2022
DOI: 10.3390/buildings12030267
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Magnesium Ammonium Phosphate Mortar by Manufactured Limestone Sand Using Compound Defoaming Agents for Improved Strength and Impermeability

Abstract: Magnesium ammonium phosphate cement (MAPC) mortar has recently risen up as high performance rapid repair material for concrete structures. But high costs of the raw materials limit its restoration and maintenance projects on a wide application range. This study proposes the use of manufactured limestone sand with lower cost and wider range of sources in replacement of quartz sand as fine aggregates to produce MAPC mortar. However, the limestone fines of manufactured sand were initially found to have negative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In Mao et al's study [13], polyether modified silicone (PMS) defoamer and its compound use with mineral admixtures Portland cement and silica fume were investigated on the effectiveness in reducing expansion and improving other properties of magnesium ammonium phosphate cement (MAPC) mortar. The results showed that the compound use of PMS defoamer and Portland cement as a new defoaming formula effectively reduced the volume expansion from 7.92% to 0.91%.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…In Mao et al's study [13], polyether modified silicone (PMS) defoamer and its compound use with mineral admixtures Portland cement and silica fume were investigated on the effectiveness in reducing expansion and improving other properties of magnesium ammonium phosphate cement (MAPC) mortar. The results showed that the compound use of PMS defoamer and Portland cement as a new defoaming formula effectively reduced the volume expansion from 7.92% to 0.91%.…”
Section: Overview Of This Special Issuementioning
confidence: 99%